THE CHALLENGES AND SOLUTIONS OF TRANSLATING PUNS AND JOKES FROM ENGLISH TO INDONESIAN - Farida Repelitawati Br. Kembaren (VISION, 2020)
Translating puns and jokes is often perceived as the mostchallenging task in translation field. The difficulties oftranslating puns emerge because the sense of humor in thepuns and jokes can be disappeared after being translated intothe target language. This study aims to see the challenges thatEnglish Education Department’s students have as well as thesolutions they can implement in translating puns from Englishto Indonesian. This study applies qualitative method withcontent analysis technique. The data were generated from thetranslation products of puns translated by English EducationDepartment students. The data were then analyzed by usingreader-response technique to find out the readers’ responsetoward the puns and jokes that have been translated intoIndonesian. After analyzing the data, the results indicate thatmost students experienced difficulties to translate the punsfrom English to Indonesia. The biggest challenge that thestudents encountered is not only in translating the culturalhumor, but also in translating the linguistic humor and theuniversal humor. Students who implement free translationmethod and domesticating ideology were able to produce abetter target language oriented translation to let the readersunderstand the humor behind the puns and the jokes they read.These findings suggest that the solution to the challenge oftranslating puns is that students should use free translation anddomesticating ideology in translating cultural text, such aspuns and jokes.